Oil price shocks and macroeconomic condition : Case study of United Arab Emirates - Adel, Ageel (Universiti Malaysia Sarawak (UNIMAS), 2016)
The fluctuations in the global oil price and its shocks on economic activity has arose a concern among the policy makers, government, individuals, and economic practitioners to continuously debate and research on the impact of oil price shocks on economic activities of both oil rich and non-oil rich economies. To this effect, it is also pertinent to research on how the macroeconomic condition of United Arab Emirates (UAE) may be affected by the shock in oil price so that appropriate policy can be taken by the government in order to avert the possible impact on the country. To this end, this study aims to examine the relationship between oil price shocks and macroeconomic condition with a case study of United Arab Emirates for a period of 1980 to 2011. The estimation methods of Autoregressive Distributed Lag (ARDL) model proposed by Pesaran and Pairwise Granger causality were adopted to determine the relationships among the variables. The findings from the study showed that there are long run relationships among the variables examined in all the models